Genetic Improvement of Chir Pine (Pinus roxburghii Sargent.) in India - a Review - Sharma, Rajesh; Kumar, Surinder; Thakur, K. S. (Indian Forester, 2006)
Pinus roxburghii Sargent (Chir pine) is the most important pine among the six indigenous pines of India. The genetic variation in Chir pine both among and within populations with regard to quantitative and qualitative aspects of inheritance, morphological, physiological, biochemical characters and gene marker studies have been studied in the past, but in isolation. The article reviews the results of various studies on different aspects of tree improvement of the species, specifically highlighting the work on isozyme analysis of the provenances and plus trees to narrow down the population/ provenance differences and their categorization based on genetic diversity, differentiation and genetic distances.